Could insects be an alternative food source? A comprehensive review - TURAN, YAVUZ; SESAL, NÜZHET CENK (My University, 2024)
According to the United Nations, more than 800 million people are exposed to starvation. It is predicted that the world population will face much more serious starvation for reasons such as global warming, diseases, economic problems, rapid urbanization, and destruction of agricultural areas and water resources. Thus, there are significant hesitations about the sustainability of food resources, and the search for alternative food sources has increased. One of the leading alternative food sources is insects. Although the use of edible insects has been accepted in some areas of the world, entomophagy is not preferred in some countries due to sociocultural conditions, health concerns, neophobia, and entomophobia. Many people do not accept the direct consumption of raw insects, but insects can be transformed into more preferred forms by using different cooking techniques. Some ground edible insects are satisfactory in terms of nutritional value and have a reasonable level of acceptability when added to products such as bread, tortilla, and pasta in varying percentages. The world market value of edible insects was estimated to be US$3.2 million in 2021 and US$17.6 billion in 2032. In this review, the current and future situation of insects as an alternative food source is comprehensively discussed.
Keywords: Yaşam Bilimleri; Hayvan Biyolojisi; Diğer; Temel Bilimler; Life Sciences; Animal Biology; Other; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; Biyoloji ve Biyokimya; ÇOK DİSİPLİNLİ BİLİMLER; BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; BIOLOGY & BIOCHEMISTRY; MULTIDISCIPLINARY SCIENCES; BIOLOGY; Multidisipliner; Multidisciplinary; consumer acceptance; edible insects; entomophagy; market value of edible insects; sustainable food source